2012
DOI: 10.1093/cercor/bhs365
|View full text |Cite
|
Sign up to set email alerts
|

Reading Front to Back: MEG Evidence for Early Feedback Effects During Word Recognition

Abstract: Magnetoencephalography studies in humans have shown word-selective activity in the left inferior frontal gyrus (IFG) approximately 130 ms after word presentation ( Pammer et al. 2004; Cornelissen et al. 2009; Wheat et al. 2010). The role of this early frontal response is currently not known. We tested the hypothesis that the IFG provides top-down constraints on word recognition using dynamic causal modeling of magnetoencephalography data collected, while subjects viewed written words and false font stimuli. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 62 publications
(98 reference statements)
13
71
0
Order By: Relevance
“…Importantly, the fact that the anterior and middle parts of the FUS and the prefrontal cortex showed a similar pattern of activation is coherent with previous studies showing intrinsic functional connections that link the ventral occipitotemporal cortex (particularly at the site of the Visual Word Form Area) with the IFG (Bitan et al, 2005;Koyama et al, 2010). However, further studies using techniques with higher temporal resolution are needed to decide whether the task-related effect that was observed in the occipitotemporal orthographic system occurred within the system itself or resulted from top-down projections from prefrontal regions as is typically assumed (Gilbert and Sigman, 2007;Price and Devlin, 2011;Twomey et al, 2011;Woodhead et al, 2014).…”
Section: Task-driven Activation Of Orthographic Phonological and Semsupporting
confidence: 86%
“…Importantly, the fact that the anterior and middle parts of the FUS and the prefrontal cortex showed a similar pattern of activation is coherent with previous studies showing intrinsic functional connections that link the ventral occipitotemporal cortex (particularly at the site of the Visual Word Form Area) with the IFG (Bitan et al, 2005;Koyama et al, 2010). However, further studies using techniques with higher temporal resolution are needed to decide whether the task-related effect that was observed in the occipitotemporal orthographic system occurred within the system itself or resulted from top-down projections from prefrontal regions as is typically assumed (Gilbert and Sigman, 2007;Price and Devlin, 2011;Twomey et al, 2011;Woodhead et al, 2014).…”
Section: Task-driven Activation Of Orthographic Phonological and Semsupporting
confidence: 86%
“…The type of topdown feedback that we propose may be neurobiologically instantiated in terms of frontal-occipito-temporal connections. Consistent with our interpretation, Woodhead et al (2012) found higher activation in the left inferior frontal gyrus for words (as compared to false fonts), together with feedback connections from the inferior frontal gyrus to the left ventral occipito-temporal cortex within the first 200 ms of stimulus processing (see also Thesen et al, 2012, for converging evidence). Likewise, Twomey, Kawabata Duncan, Price, and Devlin (2011) found that the activation of the left ventral occipito-temporal cortex, a brain structure involved in early stage processing during visual word recognition, was modulated differently by emphasizing phonological versus orthographical criteria in the lexical decision task.…”
supporting
confidence: 84%
“…Some previous studies, relying on MEG-based source reconstruction techniques, have reported that the first 140-200 ms are sufficient for visual information to contact phonological and lexical codes in the precentral cortex and inferior frontal gyrus (10,66,67) and, in turn, send feedback signals to ventral occipitotemporal regions (67). In this case, even early occipital responses at ∼150 ms could be influenced by top-down signals.…”
Section: Discussionmentioning
confidence: 94%